Traffic Communication - Borg, Joakim; Lütkeman Pukala, Samantha (2011)
The project was started in Sweden at Luleå University of Technology but carried out in Chicago in cooperation with Beyond Design Inc. Beyond Design Inc. is a consultant company who has done designs for various brands. The company has provided guidance, programs and equipment to help carry out the project. The project investigates traffic communication with the goal to see what improvements can be done within the subject’s nature, safety and technology. Traffic communication in this context means the interaction between the users in the traffic. Today this communication is mostly done through traffic lights, but in this project the focus is on the communication in traffic and what can be developed within it rather than the traffic light itself. The human senses are channels to interpret information. This project investigates if there are other ways to give and understand the same message but in another way. Today vision is the main sense used in traffic with lights and signs signaling to drivers and pedestrians. But is this still the optimal way considering the development of technology in the past decades? Through various steps in the design process like video documentation, brainstorming, evaluation process and refinement in various programs a direction for the project was set. The result is presented in a CAD model. New solutions, designs and concepts are adapted for the user where the system controlling the intersection should be adjusted after the user needs. A total centralization is the basic thought. Existing technology that are separated today is brought together to make traffic communication controlled by the users. Nature is brought in to lower the feeling of stress as well as reduce noise. In the safety aspect the traffic light device signals from which direction an emergency vehicle is approaching. The physical design of the intersection is made so that intuitive actions control the user’s behavior and structure of the crossing. Validerat; 20111029 (anonymous)